2014
DOI: 10.1097/wnr.0000000000000187
|View full text |Cite
|
Sign up to set email alerts
|

Serum β-nerve growth factor concentrations in pregnant female, nonpregnant female, and male cynomolgus monkeys

Abstract: Serum β-nerve growth factor (NGF) concentrations were determined in pregnant female, nonpregnant female, and male cynomolgus monkeys using a highly selective and sensitive immunoaffinity liquid chromatography-tandem mass spectrometry assay. NGF was significantly higher in pregnant monkeys than in nonpregnant female and male monkeys. NGF increased over pregnancy (mean NGF±SD: 541±448, 1590±520, and 3560±1430 pg/ml during the first, second, and third trimesters, respectively). These data will aid in further unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…This increase was greater than the observed variability established during assay qualification. Previous studies have shown small, non-significant changes in circulating mature NGF levels during human gestation 59 , 60 and while the data contained in this study does show a small yet significant increase in tNGF over gestation, it is in general agreement with values published previously 48 , 59 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This increase was greater than the observed variability established during assay qualification. Previous studies have shown small, non-significant changes in circulating mature NGF levels during human gestation 59 , 60 and while the data contained in this study does show a small yet significant increase in tNGF over gestation, it is in general agreement with values published previously 48 , 59 .…”
Section: Discussionsupporting
confidence: 92%
“…Previous work using the LCMS assay for NGF demonstrated a large and continuous increase in NGF expression (up to ~ 78×) during gestation in cynomolgus monkeys, with no difference in circulating levels between male and the non-pregnant female control populations 48 . Though a large increase in circulating tNGF levels has been shown in cynomolgus monkeys 48 , this phenomenon has not been reported in human pregnancy which seems to point towards species specific differences during pregnancy.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Tometten et al (2005) reported that NGF is mandatory for the success of pregnancy as it constitutes a functional link between the nervous, immune and endocrine systems and translating environmental or endocrine signals (Tometten et al, 2005). It has been reported that higher NGF levels in pregnancy which are progressive as trimester progresses in monkeys as compared to non pregnant monkeys (Neubert et al, 2014).…”
Section: Introductionmentioning
confidence: 99%